Is COVID-19 an Advantage to Disadvantaged Groups? Evidence from Administrative Data on Working Hours in Turkey - Sibel Selim; Şenay Üçdoğruk Birecikli; Gökhan Özkubat (Journal of Economy Culture and Society)
This paper examines the effects of COVID-19, which caused a recession in many fields in 2020, on the working hours of workers. Using the quarterly microdata set of the TurkStat Household Labour Force Surveys and the Oxford COVID-19 Government Response Tracker (OxCGRT) database, we found that the greatest work loss occurred in the second quarter of 2020 when the first shock of the pandemic was experienced. We also show that the stringency of the restrictions affects work loss. We present evidence that women, youth, informal, and temporary workers, who are classified as disadvantaged groups in the Turkish labor market, lost fewer working hours in the first period of the pandemic. Our quantitative analysis suggests that workers between the ages of 15 and 24 lost at least 2 hours less in the second quarter of 2020. Compared to the pre-pandemic period, working-hour gaps between formal and informal workers and permanent and temporary workers closed by about 1.5 hours in the same quarter. In addition, it is predicted that as the stringency of the restrictions increases by 10 points, working-hour gaps between the genders will be lessened by about 0.1 hours. The elderly, university graduates and those working in small businesses are the groups most affected by the pandemic. We also find that the balance between hourly wages and working hours has been disrupted at the beginning of the pandemic.